In Silico Exploration of Bioactive Compounds from Dracaena cochinchinensis as Potential Inhibitors of Streptococcus pyogenes Inosine-5'-Monophosphate Dehydrogenase (IMPDH) - Septi Handayani; Nawan Nawan; Agnes Toemon (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The emergence of multidrug-resistant Streptococcus pyogenes presents a significant global health threat, demanding the urgent discovery of novel antibacterial agents. This study utilized a comprehensive in silico framework to investigate 17 compounds from the traditional medicinal plant Dracaena cochinchinensis as potential inhibitors of Inosine-5'-monophosphate dehydrogenase (IMPDH), a validated antimicrobial drug target. The workflow included predictive modeling of physicochemical properties, pharmacokinetics (ADME), toxicity profiles, and molecular docking simulations to elucidate binding affinities and interaction patterns within the enzyme's active site. Physicochemical analysis revealed that 11 of the 17 compounds exhibited drug-like properties. Molecular docking identified several ligands with high binding affinities, notably Isopimaric acid (-8.2 kcal/mol) and Cochinchinenene D (-8.1 kcal/mol), whose stability was mediated by interactions with key catalytic residues. ADMET predictions indicated that most compounds possess favorable pharmacokinetic profiles. Crucially, Isopimaric acid demonstrated a superior safety profile, with a high LD50 (5000 mg/kg), no predicted mutagenicity, and no risk of drug-induced liver injury (DILI). This computational investigation successfully identified Isopimaric acid as a standout candidate, and its combination of strong target affinity and a favorable ADMET profile positions it as a promising scaffold for the development of novel antibacterial agents against S. pyogenes. These findings provide a strong impetus for experimental validation.